Embedding Living Cells with a Mechanically Reinforced and Functionally Programmable Hydrogel Fiber Platform - Peng, Ruoxuan; Ba, Fang; Li, Jie; Cao, Jiayi; Zhang, Rong; Liu, Wan‐Qiu; Ren, Jing; Liu, Yifan; Li, Jian; Ling, Shengjie (Advanced materials (Weinheim), 2023)
Living materials represent a new frontier in functional material design, integrating synthetic biology tools to endow materials with programmable, dynamic, and life‐like characteristics. However, a major challenge in creating living materials is balancing the tradeoff between structural stability, mechanical performance, and functional programmability. To address this challenge, a sheath–core living hydrogel fiber platform that synergistically integrates living bacteria with hydrogel fibers to achieve both functional diversity and structural and mechanical robustness is proposed. In the design, microfluidic spinning is used to produce hydrogel fiber, which offers advantages in both structural and functional designability due to their hierarchical porous architectures that can be tailored and their mechanical performance that can be enhanced through a variety of post‐processing approaches. By introducing living bacteria, the platform is endowed with programmable functionality and life‐like capabilities. This work reconstructs the genetic circuits of living bacteria to express chromoproteins and fluorescent proteins as two prototypes that enable the coloration of living fibers and sensing water pollutants by monitoring the amount of fluorescent protein expressed. Altogether, this study establishes a structure–property–function optimized living hydrogel fiber platform, providing a new tool for accelerating the practical applications of the emerging living material systems. A novel sheath–core living hydrogel fiber platform is introduced, wherein synthetic biology and microfluidic spinning are integrated, offering enhanced programmability, mechanical robustness, and functional diversity. The platform's innovative design allows for tailored porous architectures and improved mechanical performance, alongside applications like coloration of fibers and water pollutant detection through modified bacterial gene circuits.